2016
DOI: 10.1242/jcs.194621
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila sensory cilia lacking MKS proteins exhibit striking defects in development but only subtle defects in adults

Abstract: Cilia are conserved organelles that have important motility, sensory and signalling roles. The transition zone (TZ) at the base of the cilium is crucial for cilia function, and defects in several TZ proteins are associated with human congenital ciliopathies such as nephronophthisis (NPHP) and Meckel–Gruber syndrome (MKS). In several species, MKS and NPHP proteins form separate complexes that cooperate with Cep290 to assemble the TZ, but flies seem to lack core components of the NPHP module. We show that MKS pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 69 publications
2
35
0
Order By: Relevance
“…Consistent with this result, the ultrastructure of BBs in β 2 t-SigD is normal, and localization of the centriolar marker GFP-PACT (Basto et al, 2006) is similar in control and β 2 t-SigD cells (Wei et al, 2008). In contrast, the TZ proteins Chibby (Cby) (Enjolras et al, 2012) and Mks1 (Vieillard et al, 2016;Pratt et al, 2016) exhibited hyperelongation in β 2 t-SigD cells (Fig. 1E), indicating that this phenotype is not unique to Cep290.…”
Section: Results and Discussion Pip 2 Is Essential For Transition Zonsupporting
confidence: 75%
See 2 more Smart Citations
“…Consistent with this result, the ultrastructure of BBs in β 2 t-SigD is normal, and localization of the centriolar marker GFP-PACT (Basto et al, 2006) is similar in control and β 2 t-SigD cells (Wei et al, 2008). In contrast, the TZ proteins Chibby (Cby) (Enjolras et al, 2012) and Mks1 (Vieillard et al, 2016;Pratt et al, 2016) exhibited hyperelongation in β 2 t-SigD cells (Fig. 1E), indicating that this phenotype is not unique to Cep290.…”
Section: Results and Discussion Pip 2 Is Essential For Transition Zonsupporting
confidence: 75%
“…Similar to β 2 t-SigD, Drosophila dila; cby and cby mutants display hyperelongated TZs (Enjolras et al, 2012;Vieillard et al, 2016). In contrast, mks1 mutants have shorter TZs (Pratt et al, 2016). Because both Cby and Mks1 are hyperelongated in β 2 t-SigD cells, PIP 2 regulates TZ length independently of an effect on Cby or Mks1 recruitment.…”
Section: Hyperelongated Tzs Exhibit Functional Defectsmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been observed that in Drosophila the ciliary projections of neurons of type I elongate through a mechanism mediated by an intraflagellar transport (IFT) mechanism [140,141], namely the compartmentalized pathway of assembly [142]. The base of the sensory cilia in Drosophila displays Y-links [68,90] and contains some conserved transition zone (TZ) module proteins [89][90][91]143]. This suggests that this region can be regarded as a typical TZ, a specialized domain found at the boundary between the basal body and the axoneme in primary cilia and directly involved in their assembly and maintenance.…”
Section: Unusual Ciliary Structures In Hexapoda Spermatocytesmentioning
confidence: 99%
“…An additional question is the elongation mechanism of the CLRs. Although the CLRs of Drosophila spermatocytes diverge from the conventional primary cilia, they share with vertebrate cilia some conserved TZ module proteins [87][88][89]143,154]. The CLRs are assembled in Drosophila by IFT-independent mechanisms [155] and it has been proposed that their grow requires components directly recruited from the cytoplasm, namely the cytosolic pathway of assembly [142].…”
Section: Unusual Ciliary Structures In Hexapoda Spermatocytesmentioning
confidence: 99%